Evidence for additive effects of virus infection and water availability on phytohormone induction in a staple crop - Davis, Thomas S.; Bosque-Pérez, Nilsa A.; Popova, Ina; Eigenbrode, Sanford D. (Frontiers in Ecology and Evolution, 2015)
Infection with phytoviruses influences plant responses to environmental stress, but the biochemical mechanisms underlying these interactions are unknown. Infection of wheat (Triticum aestivum) with a cereal virus (Barley yellow dwarf virus, BYDV) has context-dependent effects on plant productivity and survival conditional to water stress, and we hypothesized this was due to phythormone induction resulting from virus infection. We tested whether BYDV infection and water availability interact to influence hormone profiles in wheat across multiple time periods. Wheat plants were inoculated with BYDV by exposing them to infectious aphids (Rhopalosiphum padi). Concentrations of five hormones (abscisic acid, jasmonic acid, methyl jasmonate, methyl salicylate [MS], and salicylic acid [SA]) in leaf tissues were compared to concentrations in plants exposed to noninfectious aphids (sham treatment) and nondamaged control plants for five time-since-infection periods (0, 8, 16, 24, and 32 d) and two levels of water availability (0.2 and 0.8 g H20/g soil). Three important findings emerged: (1) total hormone concentrations in BYDV-infected plants exceeded concentrations in sham-treated and control plants up to 16 d following infection, after which nondamaged plants exhibited the highest concentrations of hormones; compared with nondamaged and BYDV-infected plants, hormone levels were reduced in sham-treated plants; (2) inoculation treatment affected concentrations of MS and SA: SA concentrations were increased in BYDV-infected plants, but control plants exhibited higher MS concentrations than either BYDV-infected or sham-treated plants irrespective of watering treatments and across all time periods; and (3) correlation analysis revealed no evidence of hormonal cross-inhibition. This study provides the first evidence that BYDV infection elevates both total phytohormone levels and SA in wheat in a time-sensitive manner, suggesting a potential biochemical basis for virus-induced hormonal responses that alter plant responses to environmental stress.